2013
DOI: 10.3233/jcs-130472
|View full text |Cite
|
Sign up to set email alerts
|

Provably repairing the ISO/IEC 9798 standard for entity authentication1

Abstract: We formally analyze the family of entity authentication protocols defined by the ISO/IEC 9798 standard and find numerous weaknesses, both old and new, including some that violate even the most basic authentication guarantees. We analyze the cause of these weaknesses, propose repaired versions of the protocols, and provide automated, machine-checked proofs of their correctness. From an engineering perspective, we propose two design principles for security protocols that suffice to prevent all the weaknesses. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…This attack leads to both devices accepting although neither actually pairs with the other. Similar attacks have been previously shown on other protocols [5].…”
Section: Analysis Of Passkey Entrysupporting
confidence: 83%
“…This attack leads to both devices accepting although neither actually pairs with the other. Similar attacks have been previously shown on other protocols [5].…”
Section: Analysis Of Passkey Entrysupporting
confidence: 83%
“…The proposed protocol for the trusted IoT device scenario was modeled based on existing Scyther models [64] of the ISO 9798 standard for entity authentication, which were used for the conception of SKID3 protocol [59].…”
Section: Definition 15 (Injective Agreement)mentioning
confidence: 99%
“…Cremers and Horvat [8] verified 30 key exchange protocols standardized in ISO/IEC 11770-2 [9] and ISO/IEC 11770-3 [10] with automated security verification tool Scyther [11], and found some spoofing attacks. Scyther and Tamarin Prover [12] have been also used to verify other standardized protocols such as IKEv1/v2 in IPsec [13], entity authentication protocols in ISO/IEC 9798 [14], TLS 1.3 [15], 5G-AKA [16] and smart grid authentication protocol SAv5 in IEEE 1815-2012 [17] and others. Dreier et al [26] showed verification results of industrial protocols OPC-UA and MODBUS with Tamarin Prover, and gave a modeling of sequence numbers and counters.…”
Section: Related Workmentioning
confidence: 99%